Civic Engagement and Critical Thinking Skills among Pre-Service Teachers in Multicultural Societies - Muhammad Nurfaizi Arya Rahardja; Shavira Salsabila; Achmaf Afif Fikri; Moh. Imron Rosidi; Abid Nurhuda; Anjela Karunia Amalia (International Journal of Social Sciences, Language, and Education, 2026)
In multicultural societies, pre-service teachers are increasingly expected to function as educators who are both civically engaged and critically reflective. This study examines the conceptual relationship between civic engagement and critical thinking within pre-service teacher education through a qualitative library-based research approach. Drawing on peer-reviewed literature in teacher education, multicultural pedagogy, and democratic citizenship, the study analyzes how civic engagement experiences contribute to the development of higher-order thinking and ethical awareness among future teachers. The findings indicate that civic engagement, when framed through critical and multicultural pedagogical perspectives, fosters reflective judgment, democratic values, and intercultural sensitivity. Critical thinking emerges as a mediating capacity that enables pre-service teachers to interpret civic experiences analytically and respond constructively to social complexity. The study further highlights the role of critical reflection in transforming community engagement into professional knowledge. Overall, the analysis suggests that integrating civic engagement and critical thinking within teacher education strengthens the preparation of educators capable of promoting inclusive, democratic, and socially responsive learning environments in culturally diverse contexts.